PROBLEMATIK GURU DALAM MELAKSANAKAN PEMBELAJARAN TEKS ULASAN KELAS VIII SMP ISLAM AL FALAH KOTA JAMBI - Agus Setyonegoro; Akhyaruddin Akhyaruddin; Gani Ismail Aqso (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2023)
The purpose of this research is to describe strategies used by journalists in marginalizing corruptors available in law and political rubrics of Kompas Daily examined using a discourse analysis with Theo Van Leeuwen model. This research is conducted using a descriptive-qualitative method. The research data are in the forms of transcriptions of Kompas Daily discourse texts available in law and political rubrics. Data are taken from Kompas Daily on editions of 29 may 2013 – 7 June 2013. Based on the data analysis and discussion, it can be concluded that due to the news reports on corruption crime cases, the journalists tend to marginalize corruptors. First, the exclusion strategies consist of (1) passiveness and (2) nominalization. Second, the inclusion strategies consist of (1) objectiveness, (2) nomination, (3) nomination-identification, (4) determination, and (5) individualization.  All those strategies are used by journalists to marginalize corruptors.